(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to examine the psychological happiness and academic emotions among faculty members at the University of Baghdad in terms of gender and years of service, as well as to identify if there is a correlation between psychological happiness and academic emotions. Two scales were used to collect the needed data: Riff & Singer’s scale (2008) to measure psychological happiness and Frenzal’s scale (2016) to measure academic emotions, which were administered to a sample of 46 males and 90 females collected randomly from four different faculties. The researcher used a t-test, alpha-Cronbach, and Pearson correlation coefficient to analyze the data. The results showed that the research sample had a high level of pleasure compared to anger and anxiety, which were low. There is no statistically significant relationship between psychological happiness and pleasure. There is a negative relationship between psychological happiness and both the emotion of anger and anxiety (the more psychological happiness increases, the less the emotion of anger and anxiety within the educational environment). The results also disclosed that there is no statistically significant difference between psychological happiness and academic emotions in terms of gender. There is no significant difference in terms of years of service and the emotion of anxiety and pleasure for academic emotions and psychological happiness. As for the emotion of anger, it showed a significant difference for teachers who have years of service (1–5). The researcher came out with a set of recommendations and suggestions.